Assessment of Consistency in the Functioning of Seaports of Ukraine - Sotnychenko, Lyudmila; Haichenia, Oleksandr; Omelchenko, Taras; Kuzmenko, Kateryna (Dr. Viktor Koval, 2024)
Introduction. Seaports in a state’s economies are the main levers of economic development, investment generators, and innovation demand. Modern trade ports are open systems that are influenced by many factors. During the last decades of globalization and innovative technologies, an essential factor in the competitiveness of seaports, such as the stability of the functioning of Ukraine, is gaining relevance. The improvement of port management is driven by the urgent need to apply innovative strategies and methods to ensure the development and efficiency of the port industry due to the impact of many factors affecting the stability and growth of the port system. Aim and tasks. The aim of the study is to assess the influence of various factors on the consistency of the management system of the port industry. Result. An algorithm for forming generalized stability indicators for the functioning system of the port industry is proposed. Using an entropy approach to the management indicators of the development of the port industry functioning system showed an increase in the indicators of the ship operations group by 1.07% and cargo operations by 1.01%, a decrease in the financial group by 1.65%, and a port environment by 1.30%. The application of the established approach and the defined sequence of relevant calculations will allow ports to respond sensitively to violations of the stability of their system both at the industry and individual port levels and to find answers for each group of selected influential indicators for the finance group, the ship and cargo operations group, and the port environment. The main difference between the proposed approach and the existing ones is the calculation of the overall level of functioning of the port management system, which is based on the accumulation of the values of the relevant integral indicators for groups of indicators such as finance, ship-cargo operations, and port environment. Conclusions. The operation system of the port economy can be considered from the perspective of researching its various states, which are a consequence of the dynamics of the external environment. This allows us to use such a quality of entropy by considering the final nature of the management processes of the industry. This will help determine the nature of trends that can be considered in the future when forecasting the port industry’s development directions and when making relevant comparisons in the industry at the national and global levels.